MiR-346 and TRAb as Predicative Factors for Relapse in Graves’ Disease Within One Year - Li, Jianhui; Cai, Yawei; Sun, Xiaohua; Yao, Danzhen; Xia, Jinying (Hormone and Metabolic Research, 2017)
Despite the efficacy and safety, antithyroid drug (ATD) therapy for Graves’ disease (GD) is associated with a high risk of relapse, especially within the first year. The inability to predict whether and when relapse may occur is a major problem for ATD therapy. This study was aimed to investigate potential predicative factors for GD patients after ATD withdrawal. Consecutive patients newly diagnosed with GD and treated with ATD [methimazole (MMI)] were enrolled in this study. Univariate and multivariate Cox proportional hazard analyses were used for the analysis of predicative parameters for GD relapse after MMI withdrawal. Kaplan-Meier survival analysis and log-rank test were utilized for presenting the risk of relapse. Of the 103 patients included, 67 (65.0%) remained in remission and 36 (35.0%) had a relapse within 1 year after the MMI withdrawal. The multivariate analysis suggested significant predictive factors for GD relapse: patients with higher miR-346 expressions (≥median value) at diagnosis and at cessation, and lower TRAb levels at cessation. MiR-346 at diagnosis and cessation, and TRAb at cessation could serve as predictive factors for GD relapse within 1 year after drug withdrawal.
Keywords: MiR-346; TRAb; Graves’ disease; antithyroid drugs